2021
DOI: 10.1111/ejn.15246
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5‐HT7 receptors require cyclin‐dependent kinase 5 to rescue hippocampal synaptic plasticity in a mouse model of Fragile X Syndrome

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…One such compound is LP-211 that reverses mGluR mediated long-term depression (LTD) in the hippocampus of wild type and Fmr1-KO mice and improves learning deficits as well as repetitive behavior in these mice (Costa et al, 2012(Costa et al, , 2015. Recent work from Costa et al (2021) further confirmed the LP-211 effect on mGluR-LTD and revealed that this compound requires cyclin-dependent kinase 5 to rescue abnormal plasticity in Fmr1-KO mice.…”
Section: Introductionmentioning
confidence: 99%
“…One such compound is LP-211 that reverses mGluR mediated long-term depression (LTD) in the hippocampus of wild type and Fmr1-KO mice and improves learning deficits as well as repetitive behavior in these mice (Costa et al, 2012(Costa et al, , 2015. Recent work from Costa et al (2021) further confirmed the LP-211 effect on mGluR-LTD and revealed that this compound requires cyclin-dependent kinase 5 to rescue abnormal plasticity in Fmr1-KO mice.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the activation of 5-HT receptors has emerged as a promising strategy for limiting neuroin ammation. By reducing astrocyte and microglial reactivity, 5-HT receptor activation protects the brain from in ammation-induced neurodegenerative changes [42,43]. The aforementioned studies primarily concentrated on the activation of hippocampal 5-HT receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of Cdk5 has been associated with attention deficit and hyperactivity disorder [ 110 ], epilepsy [ 111 ], and schizophrenia [ 112 ]. Cdk5 rescued hippocampal synaptic plasticity in a mouse model of Fragile X Syndrome, a genetic form of intellectual disability associated with epilepsy, autism, and mood disorders, suggesting that activation of Cdk5 activity might be a pharmacological tool to treat Fragile X Syndrome [ 113 ]. However, no association between polymorphisms in Cdk5 with autism was found in a Chinese Han population [ 114 ].…”
Section: Cdk5 Knockdown and Zebrafish Motor Neurons: Relevance To Autismmentioning
confidence: 99%